The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1007/s13193-012-0151-5
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Clinical Examination of Breast Lumps in Detecting Malignancy: A Retrospective Study

Abstract: Clinical examination is a simple method to detect breast lumps and their nature as it is inexpensive and noninvasive and if found to be accurate, might be of great value as a diagnostic tool. The aim of this study was to evaluate the accuracy of clinical examination and its contribution towards the diagnosis of a palpable breast lump. The study was record based and conducted at a University Medical College Hospital and a tertiary referral centre of South India. Patient files of those women who presented with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 11 publications
(11 reference statements)
0
12
1
Order By: Relevance
“…Sensitivity, specificity, positive and negative predictive values overall accuracy of clinical breast examination in comparison to histopathology was 90.8%, with sensitivity of 95% and specificity of 88%. 14…”
Section: Discussionmentioning
confidence: 99%
“…Sensitivity, specificity, positive and negative predictive values overall accuracy of clinical breast examination in comparison to histopathology was 90.8%, with sensitivity of 95% and specificity of 88%. 14…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the media is an important means of communication for dispensing knowledge on breast cancer 15 irrespective of a person's level of education or income 16 . The ECM that is carried out by health care professionals is a simple and non-invasive method without costs with a sensibility rate of 94.5% and specificity rate of 87.7% 17 . When it is done by trained professionals this can result in their detecting a tumor the size of one centimeter if it is superficial 17 .…”
Section: Discussionmentioning
confidence: 99%
“…The ECM that is carried out by health care professionals is a simple and non-invasive method without costs with a sensibility rate of 94.5% and specificity rate of 87.7% 17 . When it is done by trained professionals this can result in their detecting a tumor the size of one centimeter if it is superficial 17 . This could be useful in areas where late diagnosis is a reality due to a lack of resources for making diagnosis using images.…”
Section: Discussionmentioning
confidence: 99%
“…The benign and malignant breast tumour subjects were attending clinic at the surgical unit of Nnamdi Azikiwe University Teaching Hospital Nnewi (NAUTH), Anambra State. The 50 healthy female control subjects were confirmed free from breast tumours by the physician [17]. The diagnosis of breast tumour was established by histo-pathological examination of biopsy and detection of cancer associated antigen 15-3 (CA 15-3).…”
Section: Methodsmentioning
confidence: 99%